Inhibition of Corrosion of Low-Carbon Steel in Aqueous Solution of Bromide by Nitrite - K. Gomma, Gamal (Asian Journal of Chemistry, 2010)
The corrosion rates of low carbon steel in aqueous solution of potassium bromide in presence of nitrite at different temperatures and concentrations were determined. The potential ennobled as the concentration of nitrite is increased in aqueous solution of bromide. The degree of coverage of the metal surface by the adsorbed nitrite is influenced by the temperature. Nitrite remained effective at the test duration. The inhibitor shifts the corrosion potential to the anodic position and polarises both the cathodic and anodic half-reaction. The mechanism of the action of the inhibitor in aqueous solution of bromide indicates that it is an anodic inhibitor.